2022
DOI: 10.1007/s00167-022-07111-2
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative MRI signal intensity correlates functional outcomes after superior capsular reconstruction

Abstract: Purpose Superior capsular reconstruction (SCR) using fascia lata autograft has been performed for irreparable rotator cuf tear recently. The signal-to-noise quotient (SNQ) of the graft on magnetic resonance imaging (MRI) may relect the degree of graft maturity and healing. However, how SNQ changes with graft remodelling and time and whether this change correlates with postoperative clinical outcomes after SCR remain unknown. This study aimed to explore the correlation between SNQ of the fascia lata autograft a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…Kholinne et al 20,21 also reported that arthroscopic SCR with mesh augmentation contributed to better clinical outcomes and lowered graft failure rate than SCR without a mesh. Ben et al 3 also reported that the SNQ of the FLA was negatively correlated with clinical outcomes after SCR. In this study, better healing of grafts with mesh augmentation as indicated by lower SNQs was found, which may explain the improved outcomes with the use of an FLA with mesh augmentation.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Kholinne et al 20,21 also reported that arthroscopic SCR with mesh augmentation contributed to better clinical outcomes and lowered graft failure rate than SCR without a mesh. Ben et al 3 also reported that the SNQ of the FLA was negatively correlated with clinical outcomes after SCR. In this study, better healing of grafts with mesh augmentation as indicated by lower SNQs was found, which may explain the improved outcomes with the use of an FLA with mesh augmentation.…”
Section: Discussionmentioning
confidence: 96%
“…Li et al 30 reported that postoperative residual pain was associated with higher SNQs of the repaired supraspinatus tendon. Ben et al 3 found that worse clinical outcomes were correlated with higher SNQs of the FLA after SCR.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patient‐reported outcome measures (PROMs) focus on measuring outcomes after surgical procedures [30]. Statistically significant differences between preoperative and postoperative PROMs were proposed to correlate with patient‐perceived clinical benefit because statistical significance may not necessarily correlate with clinical relevance [9]. Therefore, PROMs may not be applicable to every patient; PASS and MCID may serve as better parameters because they reflect the limit of minimum improvement and threshold for satisfactory outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Pain was evaluated using a visual analogue scale (VAS), with 0 being no pain and 10 being the maximum possible pain. The functional outcomes were evaluated using the ASES score, Constant score, and SANE questionnaire [3]. A dynamometer (Mecmesin BFG 200N) was used to measure isometric strength for the calculation of the Constant score.…”
Section: Outcome Measuresmentioning
confidence: 99%